2018
DOI: 10.21061/jvs.3
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Workplace Perceptions of Military Veteran Compared to Nonveteran Employees

Abstract: Qualitative methods were used to examine differences in workplace perceptions between military veteran and nonveteran employees at the Veterans Health Administration (VHA). Prior research using employee satisfaction survey data found veteran employees reported a stronger connection to the organizational mission yet were overall less satisfied than nonveteran employees. The authors examined the open-text comments from that same survey to determine whether veteran employees identified the reasons for their disco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
(25 reference statements)
0
8
0
Order By: Relevance
“…One large study (N > 175,000) found that veterans score lower than matched nonveterans on 47 out of 49 indices of work satisfaction (Teclaw, Osatuke, & Ramsel, 2016). Veterans also frequently cite concerns about unfairness and favoritism (Yanchus, Osatuke, Carameli, Barnes, & Ramsel, 2018), possibly because of the aforementioned differences between the military and civilian organizations regarding transparency in promotion and hierarchy. Veterans are also aware of and internalize mental-health stigma (Dickstein et al, 2010).…”
Section: Confronting Stereotype and Identity Threat In Postmilitary Employmentmentioning
confidence: 99%
“…One large study (N > 175,000) found that veterans score lower than matched nonveterans on 47 out of 49 indices of work satisfaction (Teclaw, Osatuke, & Ramsel, 2016). Veterans also frequently cite concerns about unfairness and favoritism (Yanchus, Osatuke, Carameli, Barnes, & Ramsel, 2018), possibly because of the aforementioned differences between the military and civilian organizations regarding transparency in promotion and hierarchy. Veterans are also aware of and internalize mental-health stigma (Dickstein et al, 2010).…”
Section: Confronting Stereotype and Identity Threat In Postmilitary Employmentmentioning
confidence: 99%
“…A similar paucity of studies exists for workforce opportunities. What little analysis is available does not amount to much more than coarse hotspot analysis (Myers 2018) or a treatment of multivariate but nonspatial elements of interest (Elliott, Gonzalez, and Larsen 2011;Carter-Boyd 2012;Barry, Whiteman, and Wadsworth 2014;Ford 2017;Yanchus et al 2018). Our research seeks to address this gap by drawing on how the technique has been widely used in other applications.…”
Section: Application Of Suitability Analysismentioning
confidence: 99%
“…These anticipated difficulties have been partly attributed to the heroic pedestal that veterans are put on (Dillon, 2017). It is not surprising then that veterans often experience a lack of fit and belongingness in civilian organizations (Elliott, Gonzalez, & Larsen, 2011;Teclaw, Osatuke, & Ramsel, 2016;Yanchus et al, 2018).…”
Section: Moral Typecasting Of Veterans Its Consequencesmentioning
confidence: 99%